Utilização de uma planta piloto de produção de etanol para realização de aulas experimentais no curso técnico em Química do IFRN Campus Nova Cruz - Teixeira, Maria Luíza de Medeiros (2021)
The first ideas that motivated us for this study emerged since we realized that there was a potential didactic resource at the Federal Institute of Education, Science and Technology of Rio Grande do Norte (IFRN), Campus Nova Cruz, which is the pilot plant for ethanol production. Analyzing this equipment, it is verified that it can be used in several school subjects of the scientific-technological axis of the Chemistry Technical Course. However, this tool was little used in experimental classes at that institution. In order to understand the reasons for the lack of use of the pilot plant in classes, we initiated an interaction with the chemistry teachers at Nova Cruz Campus through an open questionnaire, approaching possible causes that hinder the use of the pilot plant as a teaching resource. After analyzing the responses, the need to develop support material for teachers for conducting experimental classes in the pilot plant became evident. In this perspective, this dissertation research aimed to develop a didactic sequence (SD) with experimental activities, centered on the theme of ethanol production, to promote the use of the IFRN Nova Cruz Campus pilot plant. Some assumptions of investigative experimentation and the development of skills and competences for the formation of chemistry technician were taken as the theoretical basis for the development of the didactic sequence. For data collection, standard instruments for qualitative research were used, such as questionnaires applied to students and interviews with the subject’s teacher. An observation protocol and the researcher's field notes were also used during the activities application, as a way of recording student behavior. It was observed that the proposal for the studied class promoted a significant development of some important procedural contents for the acquisition of skills and competences required of a Chemistry Technician. Furthermore, after analyzing the data collected with the Likert scale questionnaire, it was found that 96% of the answers were in line with a good acceptance of SD, showing a positive evaluation by the students. It was also evidenced the motivation of the subject’s teacher to apply SD in the next classes and the potential of its use in other disciplines.